2014
DOI: 10.1094/mpmi-02-14-0052-r
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Both Surface Attachment and Surface Recognition Requirements for Appressorium Formation by Overactive Ras Signaling in Magnaporthe oryzae

Abstract: Magnaporthe oryzae forms a highly specialized infection structure called an appressorium for plant penetration. In M. oryzae and many other plant-pathogenic fungi, surface attachment and surface recognition are two essential requirements for appressorium formation. Development of appressoria in the air has not been reported. In this study, we found that expression of a dominant active MoRAS2(G18V) allele in M. oryzae resulted in the formation of morphologically abnormal appressoria on nonconducive surfaces, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 56 publications
1
55
0
Order By: Relevance
“…In M. oryzae , the feedback between the cAMP-PKA and MAPK signaling pathways regulates appressorium morphogenesis and plant infection (Zhou et al, 2012, 2014). In C. lagenarium , cAMP-PKA signaling pathway cooperated with MAPK to regulate appressorial formation and infectious growth (Takano et al, 2000; Yamauchi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In M. oryzae , the feedback between the cAMP-PKA and MAPK signaling pathways regulates appressorium morphogenesis and plant infection (Zhou et al, 2012, 2014). In C. lagenarium , cAMP-PKA signaling pathway cooperated with MAPK to regulate appressorial formation and infectious growth (Takano et al, 2000; Yamauchi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ras proteins are small GTPases which can respond to external stimuli and activate various downstream signalling pathways for cellular responses (Zhou et al , ) and whose subcellular localization is important for their functions (Prior and Hancock, ). Interestingly, Ras proteins were widely reported to be the farnesylation targets in eukaryotic cells, so we sought to determine if the functions of M. oryzae Ras proteins are regulated by farnesylation.…”
Section: Resultsmentioning
confidence: 99%
“…Some Ras‐like proteins were found in M. oryzae , and they were used to perform farnesylation site prediction by GPS‐Lipid (http://lipid.biocuckoo.org/webserver.php) (Xie et al , ). Six RAS‐like proteins, Ras1, Ras2, rho1, rho2, rho3, rho4 and ced‐10 (Fu et al , ; Zheng et al , ; Zhou et al , ), were found to contain the C‐terminal CaaX motifs (Fig. , see Supporting Information), suggesting that they could be regulated by farnesylation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations